Identifying environmental pathways between irritability during childhood and suicidal ideation and attempt in adolescence: findings from a 20‐year population‐based study. (15th March 2021) - Forte, Alberto; Orri, Massimiliano; Turecki, Gustavo; Galera, Cedric; Pompili, Maurizio; Boivin, Michel; Tremblay, Richard E.; Côté, Sylvana M.; Geoffroy, Marie‐Claude
Abstract : Background: Irritable children are at increased risk of suicidal ideation and suicide attempt, but the underlying environmental mechanisms accounting for these associations are largely unknown. We aimed to investigate the mediating role of peer victimization and harsh parenting in the association between childhood irritability and adolescent suicidal ideation and attempt. Method: N = 1, 483 participants from the Québec Longitudinal Study of Child Development followed up from 5 months until 20 years of age (2018) with annual or biannual assessments. Irritability was operationalized using assessments of teacher‐reported temper tantrums and reactive aggression. Suicidal ideation and suicide attempt at ages 13, 15, 17, and 20 years were self‐reported. Peer victimization (self‐reported at age 13) and harsh parenting (mothers reported at age 13) were considered as potential mediators. Results: We identified four trajectories of teacher‐reported irritability symptoms from 6 to 12 years: low (74.8%), rising (12.9%), declining (7.3%), and persistent (4.9%). In adjusted models, children in the persistent and rising trajectories had, respectively, 2.81‐fold (CI, 1.27–6.22) and 2.14‐fold (CI, 1.20–3.81) increased odds of suicide attempt in adolescence, but not suicidal ideation. We found that a significant proportion of the association between irritability trajectories and suicide attempt was mediated by peer victimization (33% and 35% for rising and persistent, respectively), but there was no mediation via harsh parenting. Conclusions: Our findings suggest that peer victimization may be a key mechanism explaining the increased suicide attempt risk of children presenting with persistently high or increasing irritability. Interventions to reduce peer victimization may be helpful to reduce suicide risk among irritable children.